A FEMINIST-STYLISTIC ANALYSIS OF THE TAYLOR SWIFT SONG ENTITLED THE MAN - Caroline, Yohanna Pebrianti; Zahrani, Tasya; Sitompul, M. Riyadhil; Rangkuti, Rahmadsyah (KLAUSA (Kajian Linguistik, Pembelajaran Bahasa, dan Sastra), 2023)
The Man song by Taylor Swift focuses on kinds of feminism and explains about feminism expressed about women’s social aspects. This research is intended to find out the message of The Man song based on Mills' perspective on feminist stylistics. The lyrics in this song are the main object of research. The song presents the perspective of a woman reflecting on how her life would be different if she were a man. This research employs a qualitative content analysis by presenting data in the form of descriptions and tables. The objectives of this research include examining how the song expresses writing styles related to gender across three levels: word level, sentence level, and discourse level. It was found that The Man by Taylor Swift conveys a message about gender inequality or feminism, stereotypes, and gender roles in society. The song strongly highlights the observable differences in the lives of women and men and also double standards. The words, phrases and sentences chosen explain the gaps and challenges faced by women in society, thereby encouraging listeners to question and challenge these norms.